Planting parallel program simulation on the cloud. (5th March 2013) - Cuomo, Antonio; Rak, Massimiliano; Villano, Umberto
Summary: The writing of efficient parallel code has always been a tedious and time‐consuming process. However, the performance prediction prototype tools devised in the last decade come of age now, thanks to the availability of the almost unlimited computing power of clouds. This paper presents the practical use of mJADES, a novel environment for running multiple concurrent simulations in the cloud, to predict the performance of parallel code in multiple working conditions at once. After an introduction on mJADES and its operational aspects, the construction of parallel code performance prediction models will be dealt with. The models and the results obtained for a simple but complete and meaningful case study will be presented, discussing the accuracy obtained by simulation and the time required for performing the whole set of simulations necessary to characterize the program behavior. Copyright © 2013 John Wiley & Sons, Ltd.